(untitled) (World Bulletin of Public Health, 2024)
One of the main problems during neonatal intensive care is the early detection and correction of hemodynamic disorders. Standard clinical assessment of neonatal hemodynamic status is subjective and imprecise, highlighting the need for objective monitoring methods. Below is a review of data on the use of echocardiography performed by a neonatologist to identify hemodynamic disorders and select tactics for normalizing hemodynamics.